INFERENSI KONTEKS BERDASARKAN ANALISIS RELASI MAKNA WEBTOON “SMILE BRUSH: MY OLD PICTURES” - Pehala, Ilfan Askul; Zur, Sarjaniah; Safei, Nur Hasanah (Adabiyyāt: Jurnal Bahasa dan Sastra, 2022)
The study in this research is oriented to the analysis and description of inferences on the context and a comprehensive understanding of other linguistic variables in the text and discourse in it. The research data are lingual lexical units and phrases that show the relation of synonymy and polysemy meanings in the narrative text of the comic "Smile Brush: My Old Pictures" by Waroo, which can be accessed on the Webtoon platform. The data is processed using descriptive qualitative linguistic research characteristics combined with ethnoscience analysis. Data was occupied by the distribution method using the BUL/Direct Element Sharing technique and coding. The result states that this inference is the conclusion of cognition based on the context built by involving participants, awareness, and over-paradigmatic relations to syntagmatic other ties. This inference is the role of the association of meaning to other linguistic units in understanding the context in terminating inference. The process and conclusion of all these factors and variables show the stimulative, systemic, and holistic linguistic correlation of metafunctions and stratification of linguistic domains.